1995
DOI: 10.1016/0092-8674(95)90377-1
|View full text |Cite
|
Sign up to set email alerts
|

DNA binding and meiotic chromosomal localization of the drosophila nod kinesin-like protein

Abstract: The Drosophila no distributive disjunction (nod) gene encodes a kinesin-like protein that has been proposed to push chromosomes toward the metaphase plate during female meiosis. We report that the nonmotor domain of the nod protein can mediate direct binding to DNA. Using an antiserum prepared against bacterially expressed nod protein, we show that during prometaphase nod protein is localized on oocyte chromosomes and is not restricted to either specific chromosomal regions or to the kinetochore. Thus, motor-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 26 publications
5
102
0
Order By: Relevance
“…In addition, the Mod and Nod proteins have also been shown to associate with bicoid mRNA and to form a complex with Swa and PABP in vivo (5). However, unlike Swa and PABP, Mod and Nod do not accumulate at the anterior cortex of the oocyte, thus implicating these proteins in the transport phase of bicoid mRNA localization (5,41,42). Therefore, the proper localization of an mRNA might be mediated by distinct transport and anchoring steps involving the remodeling of the RNP at various stages during the course of localization.…”
Section: Characterization Of the Ash1 Mrna Transport Rnpmentioning
confidence: 99%
“…In addition, the Mod and Nod proteins have also been shown to associate with bicoid mRNA and to form a complex with Swa and PABP in vivo (5). However, unlike Swa and PABP, Mod and Nod do not accumulate at the anterior cortex of the oocyte, thus implicating these proteins in the transport phase of bicoid mRNA localization (5,41,42). Therefore, the proper localization of an mRNA might be mediated by distinct transport and anchoring steps involving the remodeling of the RNP at various stages during the course of localization.…”
Section: Characterization Of the Ash1 Mrna Transport Rnpmentioning
confidence: 99%
“…A putative C2H2-type zinc finger motif (Vernos et al, 1995) is also found in the amino terminus of KCBP (Figure 2). Recently some of the kinesin-like proteins have been shown to contain DNAbinding motifs (Afshar et al, 1995;Vernos et al, 1995). It has been demonstrated that kinesin-like proteins with DNAbinding motifs bind DNA and are localized on the chromosomes (Afshar et al, 1995;Vernos et al, 1995;Wang and Adler, 1995).…”
Section: Gtg'i~3atgagggaaatagtgaacaattgaacagc Ttgtt Caagc Tggtac'i~t~mentioning
confidence: 99%
“…Genetic and molecular studies of the dominant nod mutation nod DTW and its partial revertants have demonstrated that the motor domain of NOD is critical for its function (Rasooly et al, 1991(Rasooly et al, , 1994. The genetic and cytological characterizations of NOD strongly suggest that it exerts a plateward (or antipolar) force (Rasooly et al, 1991(Rasooly et al, , 1994Theurkauf and Hawley, 1992;Afshar et al, 1995a;Karpen et al, 1996;Matthies et al, 1999) and NOD is found along the surface of meiotic chromosomes (Afshar et al, 1995a). Assuming that the polarity of MTs in the oocyte meiosis I spindle is canonical, NOD must act as either a plus-end-directed motor or as a brake.…”
Section: Introductionmentioning
confidence: 99%